The Influence of the Use of Interactive Learning Media on Elementary School Students' Science Learning Motivation - zarit, Nazarit Achwahyuni; Rosyidiana, Hafidz (Jurnal Multidisiplin Indonesia, 2025)
Learning motivation constitutes a critical determinant of academic success, particularly in science education at the elementary level (Madrasah Ibtidaiyah/MI). Despite its importance, conventional teaching methods often fail to adequately engage students and stimulate their intrinsic interest in science subjects, necessitating innovative pedagogical approaches. This study aims to determine the effect of interactive learning media on science learning motivation among MI students, comparing its effectiveness against conventional teaching methods in fostering student engagement and enthusiasm for scientific inquiry. The study employed an experimental research design utilizing a pretest-posttest control group configuration. The research sample consisted of two classes: an experimental group receiving instruction through interactive learning media and a control group taught using conventional methods. Learning motivation data were collected through a validated questionnaire instrument and analyzed using independent samples t-test to assess between-group differences in motivation levels. The findings revealed that the use of interactive learning media significantly increased science learning motivation among MI students compared to conventional instructional approaches. Statistical analysis demonstrated meaningful differences between experimental and control groups, with students exposed to interactive media exhibiting higher motivation scores across multiple dimensions including interest, persistence, and engagement with science content. Interactive learning media effectively enhances science learning motivation at the MI level, outperforming traditional teaching methods in stimulating student interest and enthusiasm for scientific learning. This study provides empirical evidence supporting the integration of interactive media into elementary science curricula. Theoretically, the findings reinforce constructivist learning principles emphasizing active engagement and multimedia stimulation in knowledge acquisition. Practically, educators and curriculum developers are encouraged to adopt interactive learning technologies as standard pedagogical tools to optimize science learning outcomes. Policy implications include institutional investment in educational technology infrastructure and professional development programs equipping teachers with competencies to effectively implement interactive media in classroom settings.